Knowledge, Attitudes of Preclinical Medical and Dental Students in Mymensingh towards “COVID-19”: A Cross-sectional Study (Community Based Medical Journal, 2023)
In 2020, a new global pandemic Coronavirus disease (COVID-19) emerged, which was caused by a new strain of coronavirus called severe acute respiratory syndrome-corona virus (SARS-COV-2). This study aims to assess the knowledge and attitudes towards COVID-19 among preclinical medical and dental students of Community Based Medical College (CBMC,B) in Mymensingh, Bangladesh. Data were collected in September 2020. The online questionnaire was created using Google Forms after reviewing previously conducted research and posted on several online platforms accessible by the students. Most of the students (93%) were medical students, and the rest 7% were studying Bachelor of Dental Surgery (BDS). The mean COVID-19 knowledge score was 9.04 (SD: 2.107, Range: 0-12), suggesting an overall 75.33% correct rate. The results showed that knowledge scores are higher in male, MBBS students but the difference are not significant. Analyses showed that the knowledge scores of 1st-year participants were significantly higher than 2nd-year students. Increased knowledge score was noticed in those who were not in direct contact with COVID-19 patients and not infected by COVID-19 than others, though the difference was insignificant (P>0.05). Half of the participants (50.2%) agreed that this disease will finally be successfully controlled. One hundred and sixty-seven participants (65%) had confidence that Bangladesh would get a vaccine soon to prevent the COVID-19 virus. The overall knowledge level of students was generally good. As the global threat of COVID-19 continues to emerge, improvement of knowledge and perceptions among healthcare students is essential.CBMJ 2023 January: Vol. 12 No. 01 P: 53-59